1993
DOI: 10.1055/s-2007-1002190
|View full text |Cite
|
Sign up to set email alerts
|

Renal Catabolism of Truncated Glucagon-Like Peptide 1

Abstract: We have searched for the contribution of the kidney to the catabolism of glucagon-like peptide-1 (7-36)amide or tGLP-1 by analyzing the disappearance of the [125I]tGLP-1 both in vivo, from the plasma of bilaterally nephrectomized (BNX), ureteral-ligated (BUL) and normal rats and in vitro from the perfusate of an isolated rat kidney system. Also, we have measured the degradation of the peptide by the isolated renal tubules. Results from in vivo studies demonstrated that the disappearance half-time (t1/2) of [12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 9 publications
(11 reference statements)
1
37
0
Order By: Relevance
“…Earlier studies already indicated that both incretin hormones are eliminated by the kidneys (12,13). This was supported by elevated plasma concentrations of GIP and GLP-1 found in patients with uremia (13a,13b).…”
mentioning
confidence: 80%
“…Earlier studies already indicated that both incretin hormones are eliminated by the kidneys (12,13). This was supported by elevated plasma concentrations of GIP and GLP-1 found in patients with uremia (13a,13b).…”
mentioning
confidence: 80%
“…Thus, it was concluded that the kidneys are not the primary site of DPPIV-mediated metabolism of GLP-1, but are important in the final elimination of its metabolites [11]. Only one study has sought to investigate the mechanisms behind the renal metabolism of GLP-1 and suggested that both glomerular filtration and tubular metabolism take place [12]. In rats, the half-life of GLP-1 was increased following bilateral ureteral ligation or nephrectomy, indicating that renal extraction of GLP-1 is not always dependent on the occurrence of glomerular filtration.…”
Section: Discussionmentioning
confidence: 99%
“…The same study also showed that renal clearance by the isolated kidney exceeded the simultaneously measured GFR, in agreement with the present study. Paradoxically however, renal clearance was almost eliminated in the non-filtering kidney [12], further underlining that additional studies are required to clarify precisely which mechanisms are involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elimination of bioactive GLP-1 from the circulation may occur via at least three different mechanisms: renal clearance, [30][31][32] hepatic clearance, 31 and degradation in the circulation by mainly dipeptidyl peptidase IV (DPP IV; EC 3.4.14.5). 33,34 The differences in GLP-1 and insulin concentrations and dynamics between AAs and C, warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%